71 Primary Fallopian Tube Endometriod Carcinoma An Uncommon HistoPathological Variant - Sunil V Jagtap; Shubham S Jagtap; Manisha Laddad; Perneet Kour (Dr. Annil Mahajan, 2022)
Endometriod adenocarcinoma at the fallopian tube is extremely rare histopathological variant of fallopian tube cancer. A 42 year postmenopausal women presenting with lower abdominal pain and bleeding. Radioimaging showed left adnexal neoplastic mass lesion. Panhysterectomy specimen on histopathology reported as endometroid adenocarcinoma of left fallopian tube with high grade stage IB as per FIGO system. We are presenting this case for its extreme rarity, clinical and histopathological findings.